REQUIREMENTS OF VISUALIZATION ALGORITHMS PROGRAMS - Pulyaev, С.В. (Journal of Information Technologies in Education (ITE), 2012)
The article deals with an urgent problem in our time – improving the effi-ciency of education and transition to bit new, but better than the current way, which has radically change